Autoaugmentation: A Feasible Option before Ileal Augmentation in Selected Cases - Altan, Mesut; Bozacı, Ali Cansu; Asci, Ahmet; Dogan, Hasan Serkan; Tekgul, Serdar (European Journal of Pediatric Surgery, 2021)
Purpose To evaluate the long-term outcomes of autoaugmentation (AA) in pediatric population.Materials and Methods The data of 59 patients (32 females and 27 males) who underwent AA between 1993 and 2018 were analyzed retrospectively. During postoperative follow-up, deterioration on renal scan and/or nonimproved hydronephrosis (HN) were described as upper urinary tract (UUT) impairment. Incontinence was described as use of diaper or pad. Preoperative urodynamic volume was divided into two as less than 50 and more than or equal to 50% expected bladder capacity (EBC). The effect of preoperative clinical factors on reaugmentation, incontinence, and UUT impairment was evaluated.Results The mean age and the median follow-up were 8.9 ± 3.6 years and 64 (12–218) months, respectively. Ten (16.9%) patients underwent reaugmentation (ureteral or ileal). UUT impairment and incontinence rates were 13.6% (8/59) and 30.5% (18/59), respectively. On multivariate analysis, less than 50% EBC was the only predictor of reaugmentation and incontinence (p = 0.013, odds ratio [OR]: 17.546 and p = 0.035, OR: 3.750, respectively). Preoperative HN was predictor of UUT impairment (p = 0.041, OR: 10.168). After AA, 51 patients used clean intermittent catheter and 27 (45.8%) patients discontinued the use of anticholinergic medication. At follow-up, eight (13.5%) patients underwent surgery after AA due to long-term complications, dissatisfaction, or poor functional results (bladder neck injection, cystolithotripsy, Mitrofanoff revision, dilatation, and injection).Conclusion AA is a viable option in selected cases with high pressure and low compliant bladders. Preoperative bladder capacity is significant for reaugmentation rate and continence. UUT impairment is related to preoperative HN.
Keywords: pediatric urologist; augmentation cystoplasty; autoaugmentation